Pengaruh Akuntabilitas, Conflict of Interest dan Komitmen Organisasi terhadap Fraud Pengelolaan Dana BLT pada Masa Pandemic COVID-19 - Pamungkas, Bintang; Helmayunita, Nayang; Honesty, Fiola Finomia (Universitas Negeri Padang, 2023)
This study aims to determine the effect of accountability, conflict of interest and organizational commitment to fraud in managing BLT funds during the Covid-19 pandemic. The population of this study were all village officials in the Air Pura sub-district. The sample used was 59 respondents with total sampling technique. This study used a quantitative method by distributing questionnaires directly. This study was tested using multiple regression analysis. The results obtained from this study indicate that accountability and conflict of interest did not have a significant effect on BLT fund management fraud during the Covid-19 pandemic, while organizational commitment had a positive and significant effect on BLT fund management fraud during the Covid-19 pandemic.